Penerapan Model Pembelajaran Two Stay Two Stray untuk Meningkatkan Keaktifan dan Prestasi Belajar Siswa Kelas VA SDN 74 Kota Bengkulu - Elvira Septianti Putri; Johanes Sapri; Pebrian Tarmizi (JURIDIKDAS, 2021)
This study aims to improve the activeness and learning achievement of VA class students at SDN 74 Bengkulu City by applying the Two Stay Two Stray learning model. The subjects of the study were students of class VA SDN 74 Bengkulu City. The research instruments were observation sheets and test sheets. The observation data analysis technique uses the formula of the average score, the highest score, the lowest score, the difference in score and the range of values for each criterion. Test data were analyzed using the formula of the average value and the percentage of classical learning completeness. Thus the application of the Two Stay Two Stray learning model can increase the activeness and learning achievement of class VA students at SDN 74 Bengkulu City.Keywords: Two Stay Two Stray Model, Active, Learning Achievement.